Pengaruh Waktu Penyemprotan Thermal Arc Spray Aluminium Terhadap Daya Lekat Lapisan Coating - Hastuti, Sri; Hadi, Isro Nurul; Pramono, Catur; Pandupradityo, Bramono; Larasanto (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2024)
Thermal spray aluminum (TSA) is a coating method used to resist corrosion, abrasion and deformation. TSA coating applications must have a minimum thickness of 80-100 µm, while for applications at temperatures of 600 – 9500 C the minimum thickness is 200 – 250 µm. The TSA layer in a position submerged in sea water will decrease by around 20 µm every year. The aim of this research is to examine variations in spraying time of 5, 10 and 15 seconds on the adhesion of the TSA coating layer. The substrate material used is AISI 1020 steel, using the #60 sandpaper hand tool surface preparation method. The preparation results were tested for cleanliness of the test samples referring to surface cleanliness ISO 5801. Surface roughness testing in this study produced a roughness of 1.852 µm. The results of the DFT test show that the longer the spraying process increases the layer thickness. The results of the pull off test show that optimal bonding results occur at a variation of 10 seconds with a strength of 8.16 MPa. In the bending test results variations of 5 and 10 seconds did not show any cracks, while in the 15 second variation there were small cracks, but based on standard practice item No. 21100 bending test no cracks and small cracks are still allowed. Keyword: thermal spray aluminium, surface preparation, DFT, pull off adhesive, bending